Avaliação dos fatores tradicionais e não tradicionais de risco cardiovascular na Síndrome de Sjogren - Balarini, Gabriela Moreira (2015)
Introduction: Patients with primary Sjögren´s syndrome (pSS) have increased prevalence of some traditional cardiovascular risk, but the carotid atherosclerosis plaque and its correlation with traditional and non traditional risk are not fully understood. Objective: To identify the association of carotid atherosclerosis plaque with the traditional cardiovascular risk, disease characteristics, cytokine profile and calprotectin in pSS. Methods: Cross-sectional study with healthy control group including 63 pSS patients and 63 controls volunteers underwent clinical, laboratory and ultrasound of carotid arteries. The carotid atherosclerosis plaque variables were identified in univariate and multivariate regression analysis. Results: Patients with pSS had a higher frequency of carotid atherosclerosis plaque (13% vs. 2%; p <0.05). Calprotectin, tumoral necrosis factor receptor 2 (TNF-R2), hepatocyte growth factor (HGF), Chemokine (C-C motif) Ligand 2 (CCL-2) and adiponectin than controls. In univariate analyses, calprotectin, the most traditional cardiovascular (age, male sex, metabolic syndrome, hypertension, hypertriglyceridemia, and serum creatinine), and some disease-associated risk factors (glucocorticoid, saliva substitute use and ESSDAI) were associated with a higher risk for plaque. In a multivariate analysis, having SSp was risk factor for atherosclerosis plaque independent of traditional risk factors (OR= 28.76, [95% confidence interval 1.69-490.19], p=0.02). Higher serum calprotectin was the only biomarker associated with carotid atherosclerosis plaque independent of creatinine and hypertension (OR=1.001 [95% CI 1.0001-1.001], p=0.023). Conclusion: Patients with pSS have higher prevalence of carotid atherosclerosis, which are modulated by higher traditional cardiovascular risk, glucocorticoid use, disease activity and calprotectin. Calprotectin is a biomarker of subclinical atherosclerosis in pSS.